International Financial Statistics, February 2017. (International Financial Statistics; International Financial Statistics ;, 2017)
This paper explores the country tables normally include data on a country's exchange rates, IMF position, international liquidity, monetary statistics, interest rates, prices, production, labor, international transactions, government accounts, national accounts, and population. The International Financial Statistics (IFS) contains country tables for most IMF members, as well as for Anguilla, Aruba, the Central African Economic and Monetary Community (CEMAC), Curacao, the currency union of Curacao and Sint Maarten, the Eastern Caribbean Currency Union (ECCU), the euro area, Montserrat, the former Netherlands Antilles, Sint Maarten, the West African Economic Monetary Union (WAEMU), West Bank and Gaza, and some non-sovereign territorial entities for which statistics are provided internationally on a separate basis. Also, selected series are drawn from the country tables and published in area and world tables. Selected series, including data on IMF accounts, international reserves, and international trade, are drawn from the country tables and published in world tables as well.